Microstructure development, mechanical properties and underlying mechanism of micro-TiN-reinforced AlSi10Mg composites fabricated by selective laser melting - Huang, Xu; Wang, Lu; Huang, Weidong; He, Dongdong; Cheng, Xuheng; Xu, Xiaopeng; Chen, Xinxi; Qin, Shuaishuai; Huang, L.-H. (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
In this study, aluminum matrix composites reinforced with micro-TiN are fabricated via the selective laser melting (SLM) technique. The effects of the TiN content on the densification, microstructure evolution, crystal textures, and mechanical properties are investigated. The results show that the relative density of composite samples with 0–3 wt. % TiN is higher than 98% and further increasing the TiN content results in a decrease in their relative density. The TiN particles are distributed uniformly and wetted with the AlSi10Mg matrix in the form of a graded interfacial layer. The TiN particles refine the matrix grains and significantly weaken the preferred (001) texture by promoting a heterogeneous nucleation process. Compared with those of the AlSi10Mg alloy, the microhardness, tensile strength and wear resistance of the TiN/AlSi10Mg composite are improved. The excellent mechanical properties of the Al matrix composites are attributed to the dispersion strengthening of the TiN particles and the fine-grain strengthening of the matrix. The optimal TiN content is found to be 3 wt. %, at which the fabricated samples exhibit excellent mechanical performance (132.4±4.1 HV for hardness and 379.7±4.6 MPa for tensile strength) with a low friction coefficient of 0.49.
Keywords: Selective laser melting; TiN/AlSi10Mg composites; Microstructure development; Mechanical properties